Validity and Reliability Diagnostic Test Computational Thinking Based on Local Wisdom - Ria, Reny Refitaningsih Peby; Susilowati, Dyah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the validity and reliability of the diagnostic test instrument used to measure computational thinking skills based on local wisdom. This method of research is instrument development research. The subjects of this research were students of computer science and information technology undergraduate programs at Bumigora University, totaling 108 students using a random sampling technique. Data collection techniques using tests. The data analysis technique of instrument content validity was determined based on Aiken's V formula, instrument construct validity using EFA, and instrument reliability using Cronbach Alpha. Based on the results of this research, the content validity of the instrument has a high validity index, the construct validity of the instrument items is declared feasible, and the reliability of the instrument has a high-reliability coefficient. So, this instrument is declared valid, reliable, and suitable for use to measure local wisdom-based computational thinking diagnostic tests.